FORMALI ZMA S IR FENOMENOLOGIJA V. SEZEMA NO ESTETIKOJE. - Jonkus, Dalius (Problems / Problemos, 2018)
The purpose of this article is to analyze the connection between formalism and phenomenology in Vasily Seseman's aesthetics. In the articles "Aesthetic Evaluation in the History of Art" (1922), "The Nature of Poetic Image" (1925), "Art and Culture" (1927), Seseman discusses the formalist concept of art. However, the most complete critique of the formalist conception of art is revealed in Aesthetics (1970). In this book, he presented the most comprehensive conception of aesthetic structure. In this paper, I firstly analyze the most important features of the formalist history of art, and then I explore how Seseman transforms the concept of artistic form into a conception of aesthetic structure. I argue that formalistic analysis of art transforms the concept of artistic form into a style. This style is nothing less than the experience of being in the world. Seseman abandons the dualistic separation of sensory material and intelligible form, and instead offers the concept of aesthetic structure. He reveals the relationship between the sensory structure of an aesthetic object and the perceiving subject. Aesthetic value can be revealed as meaningful only with the participation of a subject and with the necessary contemplative attitude. Analysis of art must cover not only individual structures of the object, but also the phenomenological analysis of perception. The combination of formalism and phenomenology is a peculiar characteristic of Seseman's aesthetics. The structural analysis reveals the systematic coherence among the artistic creator, work of art, and its perceiver.